Understanding Germane Cognitive Load Sustainability in Jigsaw-Based Collaborative EFL Tasks - Milda Ningsih Samir; Baso Jabu; Ryan Rayhana Sofyan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Although collaborative learning is widely used in English as a Foreign Language (EFL) classroom, limited research has examined how repeated jigsaw-based collaborative tasks sustain students' germane cognitive load over time. Unlike previous studies focusing on learning outcomes or increases in cognitive load, this study investigates the sustainability of germane cognitive load as an indicator of productive cognitive engagement. An explanatory repeated-measures design was conducted with 20 eleventh-grade students participating in four jigsaw-based collaborative EFL sessions. Data were collected through an adapted germane cognitive load questionnaire, classroom observations, and interviews. Quantitative findings showed that germane cognitive load remained at a moderate-to-high level, with no statistically significant difference between the mid-task and post-task phases, t(19) = −0.297, p = .770, indicating sustained rather than increased productive cognitive engagement. Qualitative findings revealed that task familiarity, peer explanation, information organization, and teacher facilitation supported this sustained engagement. These findings extend collaborative EFL and cognitive load research by suggesting that instructional effectiveness may be reflected not only in improved learning outcomes but also in sustaining productive cognitive engagement. For EFL teachers, structured and recurring jigsaw-based collaborative tasks may help maintain meaningful learning throughout the instructional process.